Knowledge of Mother-To-Child Transmission of HIV Among Pregnant Women Attending a Health Centre in Addis Ababa - Shenega GK; Ibrahim AA; Takele MK; Birri DJ (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2024)
Background: Mother-to-child transmission (MTCT) of HIV is the primary source of HIV infection in children younger than 15 years. The knowledge of pregnant women about MTCT and its prevention is essential in the control of MTCT of HIV. Objective: To assess the knowledge of Mother-to-Child Transmission of HIV (MTCT) and the prevention of MTCT (PMTCT) of HIV among pregnant women attending the antenatal clinic at the Wereda 04 Health Center, Kolfe Keranio sub-city, Addis Ababa, Ethiopia. Methods: This study used a cross-sectional design. It used systematic random sampling to select 231 participants from the clinic attendees. Data were collected using a semi-structured questionnaire. Binary logistic regression was used to determine the association between variables. Results: About 78.1% and 74.6% of the participants knew MTCT and PMTCT of HIV, respectively. Close to half (43.5%) agreed that MTCT of HIV could occur through breastfeeding, 33.5 % agreed it could be transmitted during pregnancy, and 23% agreed it could be transmitted during labour and delivery. Nearly 75% knew that MTCT of HIV is preventable, but only about half (47.9%) knew that MTCT is preventable through antiretroviral therapy (ART). The knowledge of pregnant women about MTCT and PMTCT was associated with place of residence as it was lower in rural women. Conclusions: Some of the participants were not knowledgeable about MTCT and PMTCT of HIV. Effective health education is recommended for women of reproductive age to reduce the MTCT of HIV.